Peran Cultural Intelligence dalam Manajemen Sumber Daya Manusia Internasional: Perspektif Teoretis dan Empiris - Chandra Ibadurrahman; Michael Harianto, Bryan; Prilly Fidelya Putri; Ari Anggarani (Lembaga Pengembangan Kinerja Dosen, 2026)
Globalization has driven increased mobility of the workforce across countries and expanded interactions between individuals from diverse cultures. This situation demands a high level of adaptability from both employees and organizations, making Cultural Intelligence (CQ) a strategic competency in International Human Resource Management (IRM). This literature review article discusses the concept of CQ, its four dimensions, theoretical foundations, and empirical findings demonstrating its relevance in IRM practice. Various studies have shown that CQ plays a significant role in the global recruitment process, the effectiveness of cross- cultural training, the success of expatriate assignments, and increased collaboration in multicultural teams. Individuals with high CQ have been shown to have better cultural adaptability, are able to build effective cross- cultural communication, and demonstrate more stable performance in international work environments. In addition to providing strategic benefits, this article also identifies several challenges in implementing CQ in multinational companies, such as limited formal training programs, cultural bias in selection, and differences in work norms across countries. Overall, this review confirms that developing CQ is a crucial element in creating effective global HR management that is responsive to cultural dynamics.